Effects of a training in positive language in a group of family parents - Arbulú Colona, Ricardo (2004)
OBJECTIVES: The raised objectives aimed to inside modify the parental language of the continuous positive-negative; to describe the changes in the perception that the parents have of themselves, by referring to the style to express itself; to describe the changes in the perception that the children have of their parents, by referring to the style to express itself and finally to describe the changes with regard to the terminology more used by the parents, in reference to the form to communicate with the children. DESIGN: Of unique Group with measurement before and later, made in families corresponding to the students of 1er year of secondary of the America School of the Callao. MATERIAL AND METHODS: The sample was based on the criterion of discrimination by participation, invited the 120 families of who 70 registered, after a drawing a total of 24 was selected to 8 families by c1assroom, doing. The Scale of Parental Language was used and in addition the Positive Parent program was designed, in order to optimize the verbal conduct of the parents in relation to its children. RESULTS: It is appraised that there were significant changes in 4 of the 20 items of the Scale of Parental Language. CONCLUSIONS: After applying Program PPP, it is appraised changes in V.D. Being able to conclude in the following thing: the Positive Parent program, modifies the verbal conduct of the parents. As it details of this affirmation we can add that. As much from the perspective of the participant parents, like from the perspective of its children, a change in the parental verbal conduct occurred, considering the scores global.